An Improved LEACH Algorithm Based On Fuzzy C-Means Algorithm And Distributed Cluster Head Selection Mechanism. - Hassan, Ali Abdul Hussian; Othman, Mohd Fairuz Iskandar; Md Shah, Wahidah; Husien, Ali Mohamed; Hassan, Hayder Abdul Hussien (Science And Engineering Research Support Society, 2019)
The beneficial capability of Wireless Sensor Networks (WSNs) to check numerous types of environmental settings via detection mechanisms on the physical state of matters discovered through researches, has attracted great interest in many quarters. Significant necessities in a majority of applications related to sensor networks are the extensive duration of network lifespan. Towards the fulfillment of such requirements, the clustering sensor nodes is an efficient method for the purpose of achieving these ends. The fundamental goal of WSN routing protocol are in maintaining the equilibrium of network energy usage, and in stretching the total network lifespan. The most famous protocol that utilized clustering technique is Low Energy Adaptive Clustering Hierarchy (LEACH). In LEACH algorithm, the random manner is used to select specific nodes as a cluster heads. In addition, the resulting clusters suffer from an imbalance in cluster size. In this study, the LEACH issues are solved by utilizing Fuzzy C-means algorithm (FCM) to form balanced clusters,which is followed by the selection of the cluster head in each cluster according to the energy of nodes and distance to the cluster centroid. The comparison of therecommended algorithm with LEACH algorithm is conducted, in relations to energy consumption and network lifetime. The result showed that our proposed algorithm has further advantage over LEACH